ISLAM DAN PANCASILA DALAM PERTARUNGAN IDEOLOGI DUNIA: Perspektif Sosiologis - Nur Syam; S. Maryam Yusuf (Dialogia, 2020)
Abstract: This article discusses the relationship between Islam and Pancasila in the midst of the struggle for world ideology that continues to exist in the midst of the nation state. In the past, ideological battles took place between the United States and its allies with the Soviet Union and its allies. After the destruction of communist ideology in Eastern Europe under the rule of the Soviet Union, the ideology of capitalism seemed to be a single ideology which ruled over countries in many countries. Indonesia, which has Pancasila as an ideology of nationality, is certainly also suitable in the battle arena. In Indonesia, there was also an internal battle between political Islam, moderate Islam and Nationalist Islam. This position is interesting to be observed in the present and future era, in its consideration with how to practice Islam on the one hand with the practice of Pancasila on the other. So far many views have been expressed between Islam and Pancasila. Through library research by studying content analysis, it is concluded that the ideology of Pancasila has strength as a counterweight between ideological battles both internally and internationally. Pancasila has proven to be a unifying ideology for the Indonesian people.الملخص:كتبت هذه المقالة لأجل التّصور عن حضور علاقة الإسلام ومبادئ الخمسة وسط مبارة الإيديولوجية العالمية. فمن المعلوم، حدث مبارة الإيديولوجية العالمية الماضية بين دولة Amerika Serikat وحليفتهم مع دولة Uni Soviet وحليفتهم. وعندما الإيديولوجية الشيوعية للدول بأوروبا الشرقية هالكة، فأصبحت الإيديولوجية الرأسمالية أحد الإيديولوجية المستخدمة في مختلف الدّول. ولكن، لا يشترك دولة إندونيسيا وسط هذه المبارة. لأنّ الإيديولوجية المستخدمة في دولة إندونيسيا هي المبادئ الخمسة. ولكن الواقع، حدثت المبارة الداخلية بإندونيسيا بين الإسلام السياسية والإسلام الوسطية والإسلام الوطنية. فأصبحت المشكلة الواقعة حالية وآتية بإندونيسيا جذّابة للبحث، ولاسيّما المشكلة في تنفيذ شريعة الإسلام بجانب تنفيذ المبادئ الخمسة كإيديولوجية الدولة. وبنسبة إلى آراء الجامع، فتبدو موقع الإسلام ومبادئ الخمسة في حالة المتطلبة وليست متناقضة. وبالإضافة إلى تنفيذ الدراسة المكتبية بنهج التحليل السياقي، فأخذا الكاتبان على النتيجة الآتية: استحقت الإيديولوجية بالمبادئ الخمسة القوّة لتوازن الإيديولوجية الدّاخلية من هجوم الإيديولوجية الدّولية. وبالإضافة إلى ذلك، أصبحت المبادئ الخمسة كالإيديولوجية لتوحيد الدولة الإندونيسيا.Abstrak: Artikel ini menggambarkan tentang relasi Islam dan Pancasila di tengah pertarungan ideologi dunia yang terus hadir di tengah negara bangsa. Di masa lalu, pertarungan ideologi terjadi antara Amerika Serikat dan sekutunya dengan Uni Soviet dan sekutunya. Pasca kehancuran ideologi komunis di Eropa Timur di bawah kekuasaan Uni Soviet, maka ideologi kapitalisme seperti menjadi ideologi tunggal yang menguasai negara-negara di banyak negara. Indonesia yang memiliki Pancasila sebagai ideologi kebangsaan tentu juga berada di dalam arena pertarungan tersebut. Di Indonesia, secara internal juga terjadi pertarungan antara Islam politik, Islam moderat, dan Islam Nasionalis. Posisi ini yang menarik untuk dicermati di era sekarang dan akan datang, dalam kaitannya dengan bagaimana mengamalkan Islam di satu sisi dengan pengamalan Pancasila di sisi lain. Sejauh ini banyak pandangan yang menyatakan bahwa antara Islam dan Pancasila bukanlah berada di dalam posisi berlawanan tetapi saling membutuhkan. Melalui penelitian kepustakaan dengan pendekatan content analysis, maka disimpulkan bahwa ideologi Pancasila memiliki kekuatan sebagai penyeimbang di antara pertarungan ideologi baik secara internal maupun internasional. Pancasila telah membuktikan bisa menjadi ideologi pemersatu bagi bangsa Indonesia.